Lewis Base Promoted, Direct 1,4-Conjugate Addition to Quinone Imine Ketals: Efficient Access to Unsymmetrical Diaryl Sulfones - Liu, Teng; Liu, Jianjun; Shen, Xianfu; Xu, Jianbin; Nian, Beifang; He, Ni; Zeng, Shunqun; Cheng, Feixiang (Synthesis, 2019)
An alternative approach with eco-friendliness and high efficiency for the preparation of unsymmetrical diaryl sulfones has been developed. The strategy takes advantage of the reaction of sulfonyl hydrazides with quinone imine ketals catalyzed by DABCO (triethylenediamine) in ethanol. This transformation proceeds via a Lewis base promoted, direct 1,4-conjugate addition/sulfonylation/alcohol elimination reaction sequence. The protocol provides an efficient approach to access an array of diverse unsymmetrical diaryl and heterodiaryl sulfones, aryl alkyl sulfones and aryl vinyl sulfones in good to excellent yields.
Keywords: unsymmetrical diaryl sulfones; eco-friendliness; Lewis base; 1,4-conjugate addition; quinone imine ketals